Support Groups Versus Primary Mental Healthcare on Disability and Continuity of Care: Community Trial [Support Groups for Recovery] - Rojas-Andrade, R (SAGE Publications Inc., 2026)
Based on the need to implement strategies to reduce recovery gaps in mental health with the community as axes of recovery, the objective of the present study was to assess the impact on psychosocial disability and care continuity in individuals with suicidal behavior, of the clinical and community components of the Mental Health Gap Action Program (mhGAP), versus exclusive psychiatric care. For this, a controlled community trial carried out in 2023 was conducted, comprising intervention groups: Support Group (SG), mhGAP Group (mhGAPG) and a Control Group (CG). Self-report measurements were collected pretest and posttest, utilizing the Psychosocial Disability Scale and the Alberta Continuity of Care Scale. The study involved the participation of 94 individuals with a history of suicidal behavior, with 30 individuals in the SG, 34 in the mhGAP group, and 30 in the CG. Categorical variables were summarized using frequency distribution tables. Descriptive statistics were used to examine participants’ characteristics at the study outcome and estimate treatment compliance. The Mann–Whitney U Test examined differences in sociodemographic variable frequencies. The Jarque-Bera test confirmed a normal distribution for psychological variables, warranting the use of parametric tests. Differences in mean values across groups, each with two measurements per individual, were assessed using a type II repeated measures ANOVA. There were significant differences based on the intervention, with the effect being greater in the SG across all domains. Significant improvement was observed in all domains of the disability and continuity of care scale within the intervention groups. Both groups showed improvement, with better results for the SG. In conclusion, a methodology is proposed for implementing support groups based on core components, which effectively enhances psychosocial disability and the continuity of mental health care, especially in suicidal behavior. © The Author(s) 2024
Keywords: Self-help group; community networks; mental health; mental health systems/hospitals; suicide